Physical stability test and irritation test of lotion moringa oleifera leaves ethanol extract with variation concentration - Sugihartini Nining; Hibatul Wafi Candra; Aufa Na’imatul (BIO Web of Conferences)
Leaves of Moringa oleifera have sunscreen activity formulated in lotion form. The stability and safety of a cosmetic preparation must be considered. This research aimed to determine the effect of variations in the concentration of Moringa oleifera leaves extract in lotion on the irritating power and stability of the preparation. Ethanol extract from Moringa oleifera leaves was obtained by maceration method with 50% ethanol solvent. The lotion preparation contains variations extract concentrations of 1% (FI), 3% (FII), 5% (FIII). The preparations were stored in a climatic chamber at 40 ± 2°C with RH 75 ± 5% for 28 days, and then evaluated for physical stability with organoleptic, pH, and viscosity parameters. Observations were made on days 1, 7, 14, 21, 28. The lotion was evaluated for irritancy using albino rabbit test animals. Data was analyzed with Two Way ANOVA statistics and Kruskal-Wallis non-parametric statistics. The results physical stability test showed an effect of extract concentration on the pH value and viscosity of the lotion (p=0.000). Increasing the extract's concentration decreased the preparation's pH value and increased its viscosity. Moringa oleifera leaves ethanol extract lotion with 3% concentration has better physical stability than other formulas and doesn’t irritate the skin.